Frequency, entity and determinants of fatigue in Charcot–Marie–Tooth disease. (2nd December 2022) - Bellofatto, Marta; Bertini, Alessandro; Tramacere, Irene; Manganelli, Fiore; Fabrizi, Gian Maria; Schenone, Angelo; Santoro, Lucio; Cavallaro, Tiziana; Grandis, Marina; Previtali, Stefano C.; Falzone, Yuri; Allegri, Isabella; et al.
Abstract: Background and purpose: Fatigue, a disabling symptom in many neuromuscular disorders, has been reported also in Charcot–Marie–Tooth disease (CMT). The presence of fatigue and its correlations in CMT was investigated. Methods: The Modified Fatigue Impact Scale (MFIS) was administered to CMT patients from the Italian Registry and a control group. An MFIS score >38 indicated abnormal fatigue. The correlation with disease severity and clinical characteristics, the Hospital Anxiety and Depression Scale and Epworth Sleepiness Scale scores, and drug use was analysed. Results: Data were collected from 251 CMT patients (136 women) and 57 controls. MFIS total (mean ± standard deviation 32 ± 18.3, median 33), physical (18.9 ± 9.7, 20) and psychosocial (2.9 ± 2.4, 3) scores in CMT patients were significantly higher than controls. Abnormal fatigue occurred in 36% of the patients who, compared to patients with normal scores, had more severe disease (median CMT Examination Score 9 vs. 7), more frequent use of foot orthotics (22% vs. 11%), need of support for walking (21% vs. 8%), hand disability (70% vs. 52%) and positive sensory symptoms (56% vs. 36%). Patients with abnormal fatigue had significantly increased frequency of anxiety/depression/general distress (Hospital Anxiety and Depression Scale), somnolence (Epworth Sleepiness Scale), obesity (body mass index ≥ 30) and use of anxiolytic/antidepressant or anti‐inflammatory/analgesic drugs. Conclusions: Fatigue is a relevant symptom in CMT as 36% of our series had scores indicating abnormal fatigue. It correlated with disease severity but also with anxiety, depression, sleepiness and obesity, indicating different components in the generation of fatigue. CMT patients' management must include treatment of fatigue and of its different generators, including general distress, sleepiness and obesity.